PEMBINAAN DAN PEMBERDAYAAN USAHA RENGGINANG DI DESA BRE KABUPATEN BIMA NUSA TENGGARA BARAT - Sri Ernawati; Nurul Huda; Jaenab Jaenab (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
The village of Bre has a lowland and highland topographic character with an area of ​​196.61 Ha/ m2. The village of Bre is run by two rivers that directly stretched into the sea that can be directly utilized by bre community to grow crops. Ibm Program in village Bre is distimuli by problems experienced by UKM Rengginang, that is (1) UMKN Rengginan in Bre Village has not been well organized in a container organization (2). The knowledge of the makers of Rengginang is still very minimal on how to deal with competition in the market, and (3) do not understand how to make financial bookkeeping, where finance for business rengginang per day often mixed with finance for daily needs. The approach used in problems solving to entrepreneurs Rengginang in the village of Bre is through a participatory approach, by data collection entrepreneurs Rengginang, transfer science and technology through the entrepreneurship workshop as well as training and Mentoring simple bookkeeping Keyword : Entrepreneurs Rengginang, Data Collection, Entrepreneurship workshop,bookkeeping.